2019
DOI: 10.1038/s41467-019-11141-9
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional and biodegradable self-propelled protein motors

Abstract: A diversity of self-propelled chemical motors, based on Marangoni propulsive forces, has been developed in recent years. However, most motors are non-functional due to poor performance, a lack of control, and the use of toxic materials. To overcome these limitations, we have developed multifunctional and biodegradable self-propelled motors from squid-derived proteins and an anesthetic metabolite. The protein motors surpass previous reports in performance output and efficiency by several orders of magnitude, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 50 publications
(59 reference statements)
0
92
0
Order By: Relevance
“…[ 1 – 3 ] They have potential to offer transformative solutions for non-invasive, local and active medical diagnosis, therapy and intervention, as their small sizes allow them to navigate inside the deep and hard-to-reach regions of the human body. [ 4 , 5 ] A myriad of microscale mobile robots has been developed in recent years, with different actuation strategies, including magnetic,[ 6 , 7 ] electric,[ 8 ] acoustic,[ 9 , 10 ] photo-,[ 11 , 12 ] thermal,[ 13 , 14 ] and chemical[ 14 17 ] actuation, for diverse medical applications,[ 1 , 2 ] such as targeted drug delivery, minimally invasive surgery, and remote sensing. However, many scientific challenges lie ahead before such untethered microrobots are ready for clinical use, such as biocompatibility, biodegradation, navigation in complex biofluids, or penetration of biological barriers.…”
mentioning
confidence: 99%
“…[ 1 – 3 ] They have potential to offer transformative solutions for non-invasive, local and active medical diagnosis, therapy and intervention, as their small sizes allow them to navigate inside the deep and hard-to-reach regions of the human body. [ 4 , 5 ] A myriad of microscale mobile robots has been developed in recent years, with different actuation strategies, including magnetic,[ 6 , 7 ] electric,[ 8 ] acoustic,[ 9 , 10 ] photo-,[ 11 , 12 ] thermal,[ 13 , 14 ] and chemical[ 14 17 ] actuation, for diverse medical applications,[ 1 , 2 ] such as targeted drug delivery, minimally invasive surgery, and remote sensing. However, many scientific challenges lie ahead before such untethered microrobots are ready for clinical use, such as biocompatibility, biodegradation, navigation in complex biofluids, or penetration of biological barriers.…”
mentioning
confidence: 99%
“…Internal removal of microrobots produced from biodegradable materials represents another strategy, allowing the microrobots to be cleared for example by surrounding enzymes (e.g., hyaluronidases, acrosins, collagenase, trypsin, etc. ), and/or local pH-or temperature-dependent processes 64,186,187 , as illustrated recently for instance for stomatocytes 64 . However, remaining subproducts and coating materials could still induce undesired immunoreactions or toxicity effects.…”
Section: Translatability Challengesmentioning
confidence: 80%
“…Currently, several studies have demonstrated that targeted drug delivery using magnetic driving and biodegradation of microrobots are possible through in vitro and in vivo experiments. [ 15–21,63 ] However, because the microrobots are in direct contact with tissue, local toxicity can be induced. [ 15,22 ] In addition, the degraded products of the microrobot can cause an inflammatory reaction through a pH change in the body.…”
Section: Discussionmentioning
confidence: 99%